The apologetic and pastoral intentions of Ibn Qayyim al-Jawziyya's polemic against Jews and Christians - Hoover, Jon (Wiley, 2010)
The Mongol destruction of Baghdad in 1258 and subsequent Mongol incursions into Syria through the early 1300s ushered in a period of great political and religious anxiety in the Near East. The Mongol Ilkhanid rulers of Persia and Iraq corralled the Christian Armenians of Cilicia to their side and sought an alliance with the Franks in the west against the Mamlūk sultans of Syria and Egypt. The Ilkhanids converted to Islam only very slowly with the Ilkhan ruler Oljeitu (d. 1316) being particularly indecisive. Baptized a Christian, Oljeitu converted to Buddhism, then to Sunnism and finally to Shīinline imageism, which put him further at odds with the Mamlūk champions of Sunnism. The Frankish Crusaders relinquished their last Levantine territories in the late 1200s, but they continued to be a thorn in the flesh to the Mamlūks from Cyprus.